Wide Excision of a Giant Lipoma of The Upper Arm: A Case Report - Egi Ghilman Islami; Yuhantoro Budi Handoyo Sakti (Universitas Muhammadiyah Purwokerto, 2023)
A lipoma is the most typical mesenchymal tumor. Over time, lipomas can grow into substantial masses. Case, A 71-year-old woman complained of a mass in her upper right arm but reported no pain or discomfort. The mass is 13 x 11 x 6 cm in size. Histopathological analysis and a wide excision surgical approach were used. A mass more than 5 cm in diameter is considered a giant lipoma. A differential diagnosis of liposarcoma can be made using a computed tomography (CT) scan or magnetic resonance imaging (MRI). The two surgical procedures of wide and marginal excision are typically used to treat lipomas depending on the size of the lipoma mass. The histopathological examination has an important role in confirming the diagnosis. The researchers describe a lipoma tumor with a large size in the upper arm after wide excision surgery.